The variability of Lagrangian transport in the southern Benguela Current upwelling system - Ragoasha, Moagabo Natalie (Department of Oceanography, 2020)
This study analyses the physical mechanisms that impact Lagrangian pathways and transport in the southern Benguela upwelling system (SBUS),an environment in which currents are key components of many important ecological processes, including the dispersal of marine larvae. Physical advection by currents is an important mechanism for egg and larvae transport success in the SBUS since the spawning areas and recruitment areas are separated by a long distance. High-resolution numerical model simulations of the SBUS coupled with particle tracking experiments are used to investigate Lagrangian pathways between the Cape Peninsula (34◦S) and St Helena Bay(32◦S) and how they are linked to the oceanic circulation. Transport success, given by the ratio of the number of particles that reach St Helena Bay over the total number of particles released, is used quantify the alongshore connectivity between the two regions. We have identified and quantified the following physical drivers: (i) Benguela Jet, (ii) offshore Ekman transport,(iii) inner shelf poleward current, (iv) mesoscale eddies to be responsible for the spatial and temporal variability of the alongshore connectivity. The Benguela Jet was found to be the dominant driver of the connectivity at both seasonal and interannual timescales. Moreover, the presence of anti-cyclonic eddies near the shelf-edge negatively impact transport success by advecting particles into the open ocean. The opposite occurs with shelf-edge eddies as they transport particles onshore onto the shelf and the Benguela Jet contributing to positive transport success anomalies. These findings will provide a valuable information for the future studies on the role of the physical drivers that impact transport of larvae and eggs.